EFEKTIVITAS METODE CERAMAH DAN DISKUSI KELOMPOK TERHADAP PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI PADA REMAJA DI YAYASAN PENDIDIKAN HARAPAN MEKAR MEDAN - Tarigan, Amira Permata Sari (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
The problems of the adolecent’s reproductive health show an escalation year by year. Based on the survey carried out in Yayasan Pendidikan Harapan Mekar Medan in February of 2010, found 4 (four) cases of Unwanted Pregnancy in 2009-2010 and there were 8 (eight) cases of unwanted pregnancy within 5(five) last year (2005 to 2010). One of the factors assumed to be causing of the problem was lack of adolescent’s knowledge about reproductive health. This study aimed to analyze the effectiveness of lecturing and group discussion methods on adolecent’s knowledge and attitudes regarding to reproductive health in Yayasan Pendidikan Harapan Mekar Medan in 2010. This type of research was the true experimental pretest-posttest control group design. Population were students of the Yayasan Pendidikan Harapan Mekar Medan. Sample of 90 people who were divided into three groups: experimental group I were treated with lecturing method as many as 30 people, experimental group II were treated with group discussions method as many as 30 people and a control group without treatment as many as 30 people. The results showed that the highest mean difference of knowledge score (6,30) occurred in the group treated through extension with group discussion methods with standart deviation of 2,96, while the mean difference of the score in the group treated through extension with lecturing methods was 4,03 with standart deviation of 2,14. In terms of the variable of attitude, the treatment of extension with group discussion methods showed a higher score improvement (13,60) with standart deviation of 7,77 compared to the score improvement of the group treated through extension with lecturing methods which reached 7,87 with standard deviation of 5,73. The result of ANOVA test and Tamhane’s T2 test further showed that the group discussion methods was effective in improving the knowledge and attitude about reproductive health among adolescents  in Yayasan Pendidikan Harapan Mekar Medan.The health promotor is suggested to applied group discussion method when carrying out the extension on health in order to make the result desired can be optimally achieved.